Digital Multilingual Practices and Identity Negotiation on Social Media From a Critical Discourse Perspective - Putri Indah Lestari; Indra Bayu Prakoso (LIER: Language Inquiry & Exploration Review, 2026)
Purpose: This study aims to examine how multilingual practices in social media function as strategic resources for identity construction, audience management, and meaning-making in digital communication. Subjects and Methods: The study analyzes 120 multilingual social media posts collected from Instagram, X, and Facebook, complemented by 15 semi-structured interviews with active multilingual users. Data were selected using purposive sampling and analyzed through a qualitative critical discourse approach to explore linguistic patterns, communicative functions, and identity representations. Results:  The findings reveal that multilingual practices are systematically structured rather than random. Intra-sentential code-switching emerges as the dominant form, reflecting flexible and integrated language use. English is predominantly associated with professional identity, global orientation, and credibility, while local languages are linked to emotional expression, cultural belonging, and interpersonal closeness. Users strategically combine these linguistic resources to construct hybrid identities that integrate global and local dimensions. The study also identifies high levels of metalinguistic awareness, where users consciously adjust language based on audience expectations and platform norms. Additionally, language choice is closely aligned with visual elements, indicating that multilingual practices operate within broader multimodal identity performances. Conclusions: Multilingualism in social media functions as a dynamic and strategic semiotic resource, enabling users to negotiate identity and social positioning within complex digital environments.